Wahdatul Ulum Perspektif Ibnu Rusyd: Hakikat Agama dan Filsafat untuk Studi Islam Masa Depan - Nilawati Tajuddin; Muhamad Agus Mushodiq (KURAS Institute, 2024)
This paper investigates the concept of wahdatul ulum from the perspective of Ibn Rushd. The researcher utilized qualitative research with a descriptive-historical analysis method. The primary data source for this study is Ibn Rushd's magnum opus,